Adolescents' Communication on Sexual and Reproductive Health Matters with Their Parents and Associated Factors among Secondary and Preparatory School Students in Ambo Town, Oromia, Ethiopia. (18th March 2021) - Bikila, Tesfaye Shibiru; Dida, Nagasa; Bulto, Gizachew Abdissa; Debelo, Bikila Tefera; Temesgen, Kababa
Abstract : Background . Sexual and reproductive health (SRH) communication is most likely to promote healthy sexual practices and to reduce risky sexual behavior among adolescents. Communication is the principal means for parents to transmit sexual values and knowledge to their children. Although there are few studies conducted on parent-adolescent communication, there is no study conducted in the town of Ambo. This study was aimed at assessing the level of parent-adolescent communication on SRH issues and its associated factors among school students in Ambo town, Oromia, Ethiopia. Method . An institution-based concurrent mixed-method cross-sectional study was conducted among 591 secondary and preparatory school students in Ambo town from February 24 th to March 9 th, 2019. A systematic sampling technique was used to select the study subject. Data were collected through self-administered questionnaires, and FGD was conducted with parents of students. Data was entered using EpiData version 3.1 and exported to SPSS version 23.0 for statistical analysis. Binary and multivariable logistic regression analyses were used to ascertain the association using a 95% confidence interval (CI) and p value (<0.05). Results . The proportion of students who had communication on sexual and reproductive health issues with their parents was 222 (37.6%). Being female (AOR = 2.07, 95% CI: 1.40-3.07), private school (AOR = 2.77, 95% CI: 1.17-3.69), a father with secondary education (AOR = 2.93, 95% CI: 1.05-8.12) and diploma and above (AOR = 3.27, 95% CI: 1.23-8.71), considering sex education necessary (AOR = 2.83, 95% CI: 1.22-6.57), got information about SRH issues from school (AOR = 2.01, 95% CI: 1.06-2.36) and media (AOR = 2.92, 95% CI: 1.49-3.71), and mother's openness to communicate about SRH issues (AOR = 3.30, 95% CI: 1.31-4.05) were found to be significantly associated with parent-adolescent communication on SRH issues. Conclusions . The study showed that parent-adolescent communication on SRH issues is low. Being female, those from a private school, father's education, perceived importance of sex education, source of information about SRH issues (school and media), and mother's openness to communicate about SRH issues were identified to be factors associated with the communication. Therefore, the concerned body should consider the identified factors to improve the current level of parent-adolescent communication and adolescent reproductive health.